Osteoporosis and bone health - Kaveh, Kamran; Ibrahim, Rashid; Emadi, Mozhdeh; Abu Bakar @ Zakaria, Md Zuki; Tengku Ibrahim, Tengku Azmi (Medwell Journals, 2010)
Osteoporosis is a metabolic bone disorder, which is characterized by a decreased in the overall amount of bone mass. This is major public problem with 30% mortality rate within the first year following osteoporotic hip fracture. The altered microarchitectural structure of bone would lead to increased susceptibility to fractures. By improving the public health and aging of the population, the incidence of this disorder is also increasing. Different treatments costs of patients is showing an increasing trend, which implies that there should be a public education regarding this threatening abnormality. Prevention rather than treatment has to be publicized by correct instructing the population and especially in the women society. This review has a brief simple but concise outlook at osteoporosis its manifestation, treatment and prevention.